Intermittent presumptive treatment in pregnancy with sulfadoxine-pyrimethamine: A counter perspective - Nosten, F; McGready, R (BioMed Central, 2015)
© 2015 Nosten and McGready.Malaria continues to cause devastation during pregnancy. Unfortunately, there is still no clear strategy to effectively protect pregnant women and countless mothers living in malaria endemic countries are dying every year. The effective prevention of malaria during pregnancy will take much more than the so-called "Global Call for Action" for an intervention (IPTp-SP) that cannot succeed. A new and truly "global" strategy is urgently needed.